Usual physical activity in children and adolescents measured by pedometer and its association with nutritional indicators.DOI: 10.5007/1980-0037.2011v13n1p22 - Henrique Luiz Monteiro; Camila Buonani da Silva; Rômulo Araújo Fernandes; Kelly Patrícia Messias; Clara Suemi Costa Rosa; Ismael Forte Freitas Júnior (Universidade Federal de Santa Catarina, 2011)
Monitoring physical activity levels in segments of the young population has become an important topic among specialists. The objective of this study was to analyze the physical activity level of schoolchildren based on two current recommendations and to examine the association between the number of steps/day and different indicators of adiposity. The sample consisted of 162 subjects aged 10 to 18 years (65 boys and 97 girls). Body mass index and body fat percentage were calculated. The level of physical activity was quantified with a pedometer (New Lifestyles NL-2000) based on the following recommendations: Duncan et al. (male: 16,000 steps/day and female: 13,000 steps/day) and Tudor-Locke et al. (male: 15,000 steps/day and female: 12,000 steps/day). The Student t-test and one-way ANOVA (LSD post hoc test) were used for comparison between groups. A level of significance of 5% was adopted (p £ 0.05). Only 18.5% of the sample met the recommendations proposed by Duncan et al. and 25.9% met the cutoff proposed by Tudor-Locke et al. Adolescents who did not meet the cutoff proposed by Duncan had higher body fat percentages than those who did (p < 0.05). In conclusion, a high rate of the youngsters did not meet the recommendations analyzed and only one indicator of adiposity was associated with meeting one of the recommendations.